« Personne ne peut éclairer tout ce tableau » (Les pistes infinies de La plus secrète mémoire des hommes) - Nissim, Liana (Ponti/Ponts, 2024)
This essay studies the multiple and complex layering that makes up the structure of Mohamed Mbougar Sarr’ novel, La plus secrète mémoire des hommes. Published in 2021, it narrates the reconstruction of the life and the search for the work written by disappeared African writer, T.C. Elimane, whose novel generated a great misunderstanding (the story reminds of the case of Yambo Ouloguem). The novel is simultaneously a roman de quête, an adventure novel, a historical novel, a detective novel, a fantasy novel, a journal, a critical essay… Thus, this critical analysis (which focuses in detail on the initial part of the work, and then offers a synthetic overview of the whole), highlights above all its transgenericity, transculturality, metaliterality and hypertextuality. Nevertheless, the narrative distortions, the mises en abîme, the puzzling anomalies, and the plurality of narratorial figures do not preclude the novel from constructing itself according to a perfect exhaustive rigour that leaves no space for the aesthetics of deconstruction and shapelessness. Instead, it orders itself along the founding axiological lines of memory, reason, and imagination, in order to reconstruct the life and literary vocation of the deceased author, but also the challenging complexity and ethical instance of the writing of the one who narrates and the one who is narrated.